Feasibility of Developing Radiotracers for MDM2: Synthesis and Preliminary Evaluation of an 18F-Labeled Analogue of the MDM2 Inhibitor SP-141 - Satish K. Chitneni; Zhengyuan Zhou; Brian E. Watts; Michael R. Zalutsky (MDPI AG, 2021)
Murine double minute 2 (MDM2), a negative regulator of the p53 tumor suppressor protein, is overexpressed in several human cancers. Herein we investigate the feasibility of developing 18F-labeled compounds based on the small molecule inhibitor SP-141 for imaging tumor MDM2 expression levels with positron emission tomography (PET). Three nonradioactive fluorinated SP-141 analogues, 1-3, were synthesized, and their binding to the MDM2 protein was analyzed by surface plasmon resonance (SPR). One of these, a fluoroethoxy analogue, was labeled with fluorine-18 (18F) using 18F-fluorethyl bromide to provide [18F]1 and evaluated in vitro and in vivo. SPR analysis confirmed the binding of the fluorinated analogues to MDM2 at 1.25-20 µM concentrations. Cell uptake studies revealed high uptake (67.5-71.4%/mg protein) and specificity of [18F]1 in MCF7 and HepG2 cells. The uptake of [18F]1 in these cells could be modulated using 100 µM SP-141, potentially reflecting changes in MDM2 expression because of p53 activation by SP-141. [18F]1 exhibited stable uptake and retention in HepG2 tumor xenografts (~3 %ID/g) in vivo, but poor clearance from blood and other normal tissues, yielding low tumor-to-background ratios (<2) at 2 h post injection. Our results suggest that [18F]1 has suboptimal characteristics for in vivo evaluation as a PET tracer for MDM2, but warrant radiolabeling and assessment of the other fluorinated analogues synthesized in this work, 2 and 3, and potentially other molecular scaffolds for developing MDM2 targeted radiotracers.